2020
DOI: 10.1016/j.ejca.2020.04.020
|View full text |Cite
|
Sign up to set email alerts
|

The EndoPredict score predicts response to neoadjuvant chemotherapy and neoendocrine therapy in hormone receptor-positive, human epidermal growth factor receptor 2-negative breast cancer patients from the ABCSG-34 trial

Abstract: Background: Neoadjuvant chemotherapy (NaCT) and neoadjuvant endocrine therapy (NET) can reduce pre-operative tumour burden in patients with estrogen receptor (ER)positive, human epidermal growth factor receptor 2 (HER2)-negative early-stage breast cancer. This prospective translational study assessed the ability of a 12-gene molecular score (MS; EndoPredict â ) to predict response to NaCT or NET within the ABCSG-34 trial. Patients and methods: Hormone receptor (HR)-positive, HER2-negative samples from patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 24 publications
0
33
0
2
Order By: Relevance
“…Although this study is a retrospective, single-center study with a small sample size, it is signi cant as it predicted the NACT response from the core biopsy sample for the rst time using the BCT score. In addition, efforts have also been made to predict the responsiveness of neoadjuvant endocrine therapy (NET) by multigene assay 21,26 . Further studies are needed to prove the predictive potential of the BCT score response to NET in Asian patients with BC because many multigene assays have been developed with a focus on the Western population 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Although this study is a retrospective, single-center study with a small sample size, it is signi cant as it predicted the NACT response from the core biopsy sample for the rst time using the BCT score. In addition, efforts have also been made to predict the responsiveness of neoadjuvant endocrine therapy (NET) by multigene assay 21,26 . Further studies are needed to prove the predictive potential of the BCT score response to NET in Asian patients with BC because many multigene assays have been developed with a focus on the Western population 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Akashi-Tanaka et al, in a small cohort of 43 patients, also suggested that a low RS predicted better RFS than for patients with intermediate or high RS (5-year RFS, 100% vs. 84% and 73%, respectively) [70]. Using Endopredict in 83 patients treated with NET, a low-risk 12-gene molecular score (MS) was also associated with a higher RCB 0-1 rate (27%) than a high-risk MS score (8%) [47].…”
Section: Genomic Signaturesmentioning
confidence: 99%
“…Given the fairly recent use of this score, only limited data are available concerning RCB after NET. In the ABCSG-34 trial, NET-treated patients (n = 83) were less likely to achieve RCB 0-1 (18.1%) compared to NCT-treated patients (24.6%) [47]. The RCB score was used in the NeoPAL and CORALLEEN trials, which both randomized patients to receive either NET combined with a CDK4/6 inhibitor or NCT.…”
Section: Residual Cancer Burdenmentioning
confidence: 99%
“…Genomic assays have become a very useful tool for guiding adjuvant treatments in early ER+ breast cancer. The possibility of performing these assays in the core biopsy increases their utility to the neoadjuvant setting, and most of them have already demonstrated their capacity for predicting NCT response [ 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. We will now review those that have been investigated in the context of NET.…”
Section: The Role Of Genomic Assays In Netmentioning
confidence: 99%
“…However, in the neoadjuvant setting, only the molecular analysis (EP) is possible. Dubsky et al analyzed 217 samples of diagnostic core biopsies from the ABCSG-34 trial [ 106 ], in which women had already been selected to receive NCT or NET according to clinical or immunohistochemical criteria. Tumors with a low molecular score (MS) were unlikely to benefit from NCT (NPV 100% (95% CI, 66.4%–100%)), whereas a high MS predicted resistance to NET (NPV 92.3% (95% CI, 79.1%–98.4%)).…”
Section: The Role Of Genomic Assays In Netmentioning
confidence: 99%